2021
DOI: 10.1155/2021/7212075
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Free Vibration Analysis of Thick Rectangular and Elliptical Plates with Concentric Cut‐Out

Abstract: This research paper deals with a numerical method which is modified and applied, by the authors to derive an eigenvalue of a thick plate having cut-out in which geometries of plate and cut-outs are different, through a deflection matching condition by including shear deformation and rotary inertia effects, with less computational efforts and high accuracy. The modified Independent Coordinate Coupling Method (ICCM) is validated with FEM package (ANSYS) and applied to know the change in eigenvalues for a plate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As a function of time and temperature, the DSC determines material transitions. The thermal phase change of the composites is shown by the endothermic (heat absorption) and exothermic (heat release) peaks and magnitudes [19,20]. The sample shape and size, the temperature ramp, and the kind of environment can all have an impact on the results gathered by the DSC study.…”
Section: Introductionmentioning
confidence: 99%
“…As a function of time and temperature, the DSC determines material transitions. The thermal phase change of the composites is shown by the endothermic (heat absorption) and exothermic (heat release) peaks and magnitudes [19,20]. The sample shape and size, the temperature ramp, and the kind of environment can all have an impact on the results gathered by the DSC study.…”
Section: Introductionmentioning
confidence: 99%
“…Liew et al [14] and Dewangan et al [15] studied the flat and curved panel structures with cutouts and observed that geometrical parameter and cutout size are significantly influencing the structures' natural frequency. Merneedi et al [16] studied the free vibration behavior of rectangular as well as elliptical plates having cutouts. It is observed that by introducing cutout onto a structure can make it vibrate with other modes for same natural frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%